A comprehensive review on Polygonum glabrum - Raja S,; Ramya I, (International Journal of Phytomedicine, 2016)
Polygonum glabrum commonly called as dense flower knotweed is a perennial plant. It is an amphibious shrub with pink flowers and glossy brown seeds found in most parts of India. Various parts of the plant like leaves, stem, flowers and roots are used in traditional system of medicine. Traditionally, different decoctions/infusions are prepared using the plant parts and given for the treatment of rheumatism, jaundice, piles etc. From pharmacological point, the plant has been effectively screened for antihepatotoxic, antinephrotoxic, antimicrobial, anticancer, antidepressant, analgesic and antioxidant activities. The plant contains many flavonoids including diosmetin, rutin, hyperin and quercitrin. The lanceolate leaves are rich in essential oil which contains many compounds like 6, 6-dimethyl-1, 3-heptadien-5-ol, oleicacid, 9-octadecenamide, isodecyloctyl ester and 1,2,3-benzenetriol. Compounds like aliphatic, alicyclic compounds, sesqueterpenes, sterols, phenolic acids as well as other trace elements have been identified in the plant. This review provides morphological, ethnomedical, pharmacological and phytochemical data of the plant Polygonum glabrum.